Sustained censorship in IN (2026-05) (India) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in India. Data sourced from OONI.
Censorship Incident ID: IN-2026-0173. Severity: warning. Confidence: 70%